RANCANG BANGUN ALAT KONVEYOR UNTUK SISTEM SOLTIR BARANG BERBASIS MIKROKONTROLER ARDUINO UNO - I Made Niki Arijaya (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2019)
Expedition delivery of goods very much Prepared by the people of Indonesia. in freight forwarding services in Indonesia has several expeditions in existence. One of them expedition TIKI, on TIKI expedition do sorting of goods which will be thrown to courier by way of worker will estimate width, height and weight of the goods. In this study made Conveyor Tool For System Sort Item that use arduino uno with load cell sensor and utrasonik sensor. On wide readings using two ultrasonic sensors that are placed on the outside of the place. And using one ultrasonic sensor measuring height and one heavy cell sensor load. At the same time in places where the sensor will read and afterwards the items will be brought by the conveyor and bar to the specified place. From the results of the study of goods in the pilah and take appropriate kereteria in the set.